Examination of The Fiber Quality Obtained From the Observed Fiber Separation Machine in Other Manufacturing Enterprise Types (ACUMEN: INTERNATIONAL JOURNAL OF MULTIDISCIPLINARY RESEARCH, 2024)
A number of works are being carried out in our country to improve the cotton processing industry and to equip it with new technologies in line with world standards. Due to such reforms carried out in the field, cotton fiber marked "Made in Uzbekistan" occupies a worthy place in the world's leading exchanges. Our republic is one of the main countries producing and supplying the most important product - cotton and products made from it - with great export potential. As the President noted: "Uzbekistan is the main producer and supplier of cotton fiber, a product that is in high demand in the world market" [3]. Today, Uzbekistan occupies the sixth place in the world in the production of cotton fiber, and the second place in its export after the USA. One of the main requirements of the market economy is to produce competitive products, to improve the existing technological processes, and to reduce the cost of products. All this requires high knowledge, experience and entrepreneurship from specialists. Our republic considers the development of scientific and technical progress to be an urgent task of increasing production and achieving high product quality.